The potential of intellectual capital as a source of competitive advantage for banks using CART classification trees - Anielak-Sobczak, Karolina (Ekonomia i Prawo. Economics and Law, 2023)
Motivation: Most of the available analyzes on building banks’ competitiveness were based on typical financial ratios. The challenge for every modern bank is not just understanding the meaning of intellectual capital, but defining its elements and determining measures that enable its effective management, leading to the improvement and maintenance of a strong competitive position. Empirical research concerning the competitiveness of banks in Poland is increasingly focused not only on efficiency and financial indicators but more often on emphasizing the significance of the components describing the IC subsystems, which include: service quality, bank reputation, customer confidence in the financial service of a given bank and the attractiveness and comprehensiveness of its offer as significant determinants of the overall assessment of a given entity. Aim: The aim of the article is to systematize the definition of a bank’s intellectual capital and to indicate its role in building a bank’s long-term competitive position using multidimensional statistical analysis — classification tree (CART method). Results: The conducted analysis will allow to find rules (based on diagnostic indicators) classifying banks into separate groups (A, B, C). This will lead to the conclusion which indicators from the economic (EC) and intellectual (IC) capital layers have the greatest impact on the competitiveness of banks (2009–2020).